Caracterización geomorfológica e identificación de las geo amenazas por volcanismo sedimentario en el sector occidental del volcán San Diego, Canalete, Colombia (2021)
In the municipality of Canalete - Córdoba, in the village of La Lorenza, there is an important sedimentary volcanic system made up of volcanoes such as Palmar and San Diego, the western sector of the San Diego volcano being considered as the study area in the present investigation, the main objective of the study was to characterize the geomorphological features of the sector in order to provide information that favors the identification of threats due to sedimentary volcanism, this objective was achieved through the interpretation and analysis of UAV photographs by means of GIS in conjunction with field control. ; This project was worked on at a scale of 1: 500, managing to detail as many geoforms as possible in the studied area, within which taps, sauces, pools and multicrater leaks were found that could be correlated with different types of threat, thus allowing to determine that the San Diego mud volcano area studied is associated with mud gap and flow ejection threats and fires.